Study of the mechanism of the photoisomerization and photooxidation of bilirubin using a model for the phototherapy of hyperbilirubinemia - Knobloch, E; Mandys, F; Hodr, R; Hujer, R; Mader, R (Journal of chromatography, 1991)
Liquid chromatography was employed for a study of photochemical degradation of bilirubin in the complex with human albumin, using a model system in the presence of riboflavin. The concentrations of bilirubin, the photoisomers and biliverdin were monitored. The reaction mechanism was verified using a quantified mathematical model and was represented by a reaction scheme. Photoisomerization is the initial process, followed by photooxidation to degradation products of the tetrapyrrole skeleton, with formation of biliverdin as an intermediate. The blood of newborns that were irradiated for treatment of hyperbilirubinemia was studied for the sake of comparison. The effect of some biochemically important substances was followed, in view of possible inhibition of the processes. The experimental results demonstrate that riboflavin acts as a catalyst, even at the concentrations typical for its occurrence in blood. The results are discussed from the point of view of the mechanism of bilirubin degradation during phototherapy.
Keywords: novorozenec; Infant, Newborn; Photochemistry; sérový albumin; Riboflavin; Humans; světlo; matematika; hyperbilirubinemie; chemické modely; fotochemie; oxidace-redukce; Bilirubin; Phototherapy; lidé; Mathematics; Serum Albumin; Light; fototerapie; Kinetics; Isomerism; Models, Chemical; Hyperbilirubinemia; bilirubin; Oxidation-Reduction; isomerie; kinetika; riboflavin